2020
DOI: 10.1080/0284186x.2019.1711169
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a large unselected cohort of metastatic colorectal cancers in relation to primary tumor location, rare metastatic sites and prognosis

Abstract: Glimelius (2020) Molecular characterization of a large unselected cohort of metastatic colorectal cancers in relation to primary tumor location, rare metastatic sites and prognosis,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 39 publications
2
46
0
Order By: Relevance
“…These two associations could be explained by the fact that only KRAS wild-type specimens were screened for BRAF. These results coincide with the association between BRAF (but no KRAS) mutational status and the proximal colon in Chinese, Australian, and Swedish populations [8,10,40].…”
Section: Traditional Statistical Associationssupporting
confidence: 83%
See 1 more Smart Citation
“…These two associations could be explained by the fact that only KRAS wild-type specimens were screened for BRAF. These results coincide with the association between BRAF (but no KRAS) mutational status and the proximal colon in Chinese, Australian, and Swedish populations [8,10,40].…”
Section: Traditional Statistical Associationssupporting
confidence: 83%
“…The only study in an African population, conducted in Morocco, registered a KRAS mutation frequency of 23.9% [37]. Studies performed in Asian populations report KRAS mutation prevalence varying from 37.9% (Japan) to 52.7% (China), whereas NRAS and BRAF mutations prevalence are closer with China reporting 3.4% and 4.5% while Japan referring 4.2% and 5.4%, respectively [8,38], nevertheless, population-based studies report up to 20% of CRC patients with BRAF mutations [39,40]. This difference could be due since every specimen was screened for KRAS, but only those that were KRAS wild type were screened for BRAF since KRAS and BRAF mutations are generally mutually exclusive.…”
Section: Plos Onementioning
confidence: 99%
“…Vishal et al have suggested that CEA, CA-199, and the primary tumor location are independent predictors for patients with CRC [34,35]. Serum levels of CEA and CA-199 are recommended to be evaluated clinically, which plays a vital role in disease monitoring, e cacy evaluation [36].…”
Section: Discussionmentioning
confidence: 99%
“…However, the anti-VEGF agent bevacizumab may be used independent of RAS mutation status or primary tumour sidedness [9]. BRAF V600E mutations, found in about 5-12% of all mCRC cases included in clinical trials but in about 20% in unselected populationbased patient materials [10,11], also require consideration when selecting treatment regimens and in the evaluation of the prognosis; BRAF V600E-mutation generally means rapid progression and poor survival with less and/or shorter response to chemotherapy. Several tyrosine kinase inhibitors such as vemurafenib, dabrafenib, and encorafenib bind specifically to the ATP-binding domain of BRAF V600E [12].…”
Section: Recent Advances In Mcrc Treatmentmentioning
confidence: 99%
“…In mCRC, MSI-H tumours are quite rare, affecting ~4% of the trial population [28,29]. However, again, incidence of these tumours is higher (7-8%) in the background population [11,28]. Notably, atezolizumab with/without cobimetinib recently failed to achieve superior efficacy outcomes relative to regorafenib in the third-line treatment of patients with predominantly microsatellite-stable mCRC within a phase 3 randomised trial [30].…”
Section: Recent Advances In Mcrc Treatmentmentioning
confidence: 99%